Penggunaan Media Menempel Gambar untuk Meningkatkan Keterampilan Motorik Halus pada Anak Usia Dini di Tapas Cinta Rosul Sidoarjo - Khoirunnisa, Windi; Fahyuni, Eni Fariyatul (Indonesian Journal Publisher, 2020)
One of the media that is easy to work with and can improve children's fine motor skills by pasting pictures. By sticking the child becomes easier improve motor skills, as children can try to cut or tear own paper, and glue the paper to the image. This research aims to identify the use of image paste media in early childhood and know it fine motor skills through pasting pictures on PAUD in TAPAS Cinta Rosul Sidoarjo. This research uses descriptive qualitative research. Research subject There are 24 children in one class. The object of this research is fine motor skills with using image paste media. The data collection technique was carried out by observation, interview, and documentation. Data analysis and interpretation techniques are carried out induction and deduction as well as qualitative descriptive. Based on the results of research and discussion, researchers can draw conclusions about using picture paste media to improve motor skills This is smooth for PAUD at TAPAS Cinta Rosul Sidoarjo which uses stick media photos at TAPAS Cinta Rosul Sidoarjo went smoothly. In every activity paste the pictures that the teacher has done step by step as much as possible, with prepare a pattern that the child is interested in, then prepare materials and tools that are suitable for used in early childhood, up to examples of how to paste pictures with good and right, so that it gets a full response and high enthusiasm by the children. With media applications, you can paste pictures on TAPAS Cinta Rosul Sidoarjo improve fine motor skills in early childhood.